2016
DOI: 10.1097/acm.0000000000000980
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Conflict of Interest Policies at U.S. Academic Research Institutions

Abstract: Purpose Institutional conflicts of interest (ICOIs) occur when the institution or leaders with authority to act on behalf of the institution have conflicts of interest (COIs) that may threaten the objectivity, integrity, or trustworthiness of research because they could impact institutional decision making. The purpose of this study was to gather and analyze information about the ICOI policies of the top 100 U.S. academic research institutions, ranked according to total research funding. Method From May–June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…The development of guidelines to identify potential COI and the recommendation of remedies are therefore of utmost importance. A review of 100 US academic research institutions, however, revealed that only 28% had a policy dealing with institutional COI in contrast to most US medical schools that had relevant policies [77]. …”
Section: Proposal To Link Different Typologies Of Corruptionmentioning
confidence: 99%
“…The development of guidelines to identify potential COI and the recommendation of remedies are therefore of utmost importance. A review of 100 US academic research institutions, however, revealed that only 28% had a policy dealing with institutional COI in contrast to most US medical schools that had relevant policies [77]. …”
Section: Proposal To Link Different Typologies Of Corruptionmentioning
confidence: 99%
“…Indeed, a recent study by the author and colleagues (Resnik et al 2015) found that only 28 % of 100 of the top U.S. academic research institutions, ranked by total research funding, had an institutional COI policy. The study also found that having an institutional COI policy was positively associated with total research funding and that there was considerable variation in the content of the policies with regard to committee structure and reporting.…”
Section: Dealing With Institutional Conflicts Of Interest In Academicmentioning
confidence: 99%
“…The trustee committee could receive reports of institutional COIs and decide whether they should be disclosed to appropriate parties (such as funding agencies, journals, or research subjects), prohibited, or managed through additional oversight (Institute of Medicine 2009). The trustee committee could also receive reports from different parts of the institution that may have information about COIs (Resnik et al 2015). For example, most universities have formed committees to review faculty COI disclosures (Institute of Medicine 2009).…”
Section: Dealing With Institutional Conflicts Of Interest In Academicmentioning
confidence: 99%
See 2 more Smart Citations